1989
DOI: 10.1038/hdy.1989.12
|View full text |Cite
|
Sign up to set email alerts
|

Cytological basis of the B chromosome accumulation mechanism in the grasshopper Heteracris littoralis (Ramb)

Abstract: An accumulation mechanism of the standard B chromosome of the grasshopper Heteracris littoralis has been studied in a natural population located in El Saler (Valencia) by two different methods: (i) the karyologica]l analysis of the offspring from wild females and (ii) cytological observations of male and female meiosis. The transmission rate of the accessory through females obtained from crosses (0.61) was slightly lower than that obtained from direct meiotic observations of secondary oocytes (0.71). The B chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
(9 reference statements)
0
10
0
Order By: Relevance
“…Female meiotic drive has been demonstrated in the grasshoppers Melanoplus femur-rubrum (Lucov and Nur 1973;Nur 1977), Myrmeleotettix maculatus (Hewitt 1973(Hewitt , 1976, Heteracris litoralis (Cano and Santos 1989), Omocestus burri (Santos et al 1993), and Eyprepocnemis plorans (Zurita et al 1998;Bakkali et al 2002). Three of these species show all A chromosomes acrocentric, but M. maculatus and O. burri have, like many Old World gomphocerines, three biarmed pairs arisen by the fixation of three centric fusions (see Table 4 Relationship between shape of Bs and shape of As Hewitt 1979), one of which probably involved the autosome carrying the histone genes, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Female meiotic drive has been demonstrated in the grasshoppers Melanoplus femur-rubrum (Lucov and Nur 1973;Nur 1977), Myrmeleotettix maculatus (Hewitt 1973(Hewitt , 1976, Heteracris litoralis (Cano and Santos 1989), Omocestus burri (Santos et al 1993), and Eyprepocnemis plorans (Zurita et al 1998;Bakkali et al 2002). Three of these species show all A chromosomes acrocentric, but M. maculatus and O. burri have, like many Old World gomphocerines, three biarmed pairs arisen by the fixation of three centric fusions (see Table 4 Relationship between shape of Bs and shape of As Hewitt 1979), one of which probably involved the autosome carrying the histone genes, i.e.…”
Section: Discussionmentioning
confidence: 98%
“…Hewitt (1976) concluded that meiotic drive in Myrmeleotettix females was a consequence of spindle asymmetry with the B chromosome orientating towards the egg pole more often. Likewise, Cano and Santos (1988) observed in H. littoralis that in anaphase I cells one of the poles was more condensed than the other suggesting an asymmetric spindle in this species also.…”
Section: Introductionmentioning
confidence: 90%
“…Whatever mechanisms are involved, they do not affect the normal chromosomes which segregate identically in both sexes (except the X chromosome). In M. maculatus and FL littoralis the behaviour of B chromosomes in male and female meiosis is similar but, in the latter, Bs tend to migrate towards the egg pole due to an asymmetry of the spindle which makes more probable the localization of the B in the egg side than in the polar body side (Hewitt, 1976;Cano and Santos, 1988). The first meiotic division spindle of Eyprepocnemis may also be asymmetric since at late anaphase I and telophase I one pole is more condensed than the other (see figs 4 and 5), however the fact that Bs orientate in the equatorial plate indicates that there is no parallel with the cases of Myrmelotettix or Heteracris.…”
Section: And Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, grasshoppers have typically asymmetric oocyte spindles and B chromosomes are known to drive during female meiosis in some species (Hewitt, 1979;Cano and Santos, 1989;Santos et al, 1993). Thus, D. pratensis, being polymorphic for Bs and Rb fusions is an exceptional model to test the centromeric drive theory as applied to B chromosomes.…”
Section: Resultsmentioning
confidence: 99%